Application of response surface methodology for the optimization of hexavalent chromium removal using a new low-cost adsorbent - Ezechi, E.H. (Taylor and Francis Inc., 2016)
The adsorption capacity of a novel adsorbent (Ageratum conyzoide leaf powder) was investigated for Cr(VI) removal from aqueous solution. Experiments were designed with the BoxâBehnken model of the response surface methodology (RSM). Preliminary experiments were conducted to obtain the optimum range of process variables used for the BoxâBehnken model. Three independent variables (pH, initial concentration, and adsorbent mass) were examined. The results show that Cr(VI) removal was more favorable at pH 2. Increase in pH above 2 resulted in negative Cr(VI) removal. Cr(VI) removal increased when adsorbent mass was increased, but decreased with increase in initial concentration. Cr(VI) removal of 92 was obtained at pH 2 and adsorbent mass of 0.3Â g. Experiments were successfully optimized by RSM. Kinetics study correlated with the pseudo-second-order kinetic model, whereas equilibrium study was best described by the Langmuir isotherm model with maximum adsorption capacity of 437Â mg/g. Thermodynamic parameters indicate a spontaneous, exothermic, and physiosorption process. Â© 2015 Balaban Desalination Publications. All rights reserved.